2021
DOI: 10.1021/acs.jpcb.1c01661
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Monoethanolamine-CO2 Zwitterion at the Vapor/Liquid Water Interface: Implications for Low Partial Pressure Carbon Capture Technologies

Abstract: The need to chemically convert CO2 at the interface of aqueous amine solutions has become particularly relevant for the development and the broad distribution of cost-effective and near-future devices for direct air capture working at low (e.g., ambient) partial pressure. Here, we have determined the stability of a CO2-monoethanolamine zwitterion and its chemical conversion into carbamate at the vapor/liquid water interface by first-principles molecular dynamics simulations coupled with a recently introduced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Reaction () is a reversible exothermic chemical reaction, as the temperature is high, the equilibrium shifts to the left. C2H7NO+CO2C2H7NOH+CnormalO2 C2H7NOH+CO2+XC2H7NOCO2+XH+ X could be OH − , MEA or water. Assuming X is MEA, the resulting reaction is: CO2+2C2H7NOC2H7NOCO2+C2H7NOH+ Sinopoli et al, applied first‐principles molecular dynamics simulations, and investigated the stability of a CO 2 ‐monoethanolamine zwitterion and its chemical conversion into carbamate at the vapor/liquid water interface 118 . This is a newly developed improved sampling approach which showed that at the vapor/amine aqueous interface, both the zwitterion and carbamate ions are unstable, displaying the variations between homogeneous and heterogeneous CO 2 chemical conversion.…”
Section: Absorbent‐based Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction () is a reversible exothermic chemical reaction, as the temperature is high, the equilibrium shifts to the left. C2H7NO+CO2C2H7NOH+CnormalO2 C2H7NOH+CO2+XC2H7NOCO2+XH+ X could be OH − , MEA or water. Assuming X is MEA, the resulting reaction is: CO2+2C2H7NOC2H7NOCO2+C2H7NOH+ Sinopoli et al, applied first‐principles molecular dynamics simulations, and investigated the stability of a CO 2 ‐monoethanolamine zwitterion and its chemical conversion into carbamate at the vapor/liquid water interface 118 . This is a newly developed improved sampling approach which showed that at the vapor/amine aqueous interface, both the zwitterion and carbamate ions are unstable, displaying the variations between homogeneous and heterogeneous CO 2 chemical conversion.…”
Section: Absorbent‐based Technologiesmentioning
confidence: 99%
“…Sinopoli et al, applied first-principles molecular dynamics simulations, and investigated the stability of a CO 2monoethanolamine zwitterion and its chemical conversion into carbamate at the vapor/liquid water interface. 118 This is a newly developed improved sampling approach which showed that at the vapor/amine aqueous interface, both the zwitterion and carbamate ions are unstable, displaying the variations between homogeneous and heterogeneous CO 2 chemical conversion. Furthermore, with today's computational fluid dynamics and simulation techniques, we can readily analyze the capture mechanism better.…”
Section: Alkanolamine-based Carbon Capturementioning
confidence: 99%
“…Related work by Richmond and co-workers used vibrational sum frequency generation (SFG) spectroscopy and molecular dynamics (MD) simulations to study the surface behavior of the CO 2 sorbent monoethanolamine under CO 2 gas flow conditions with a goal to understand the complex interfacial chemistry behind CO 2 capture from concentrated streams, such as flue gas. 11 Furthermore, the stability of the CO 2monoethanolamine zwitterion formed during the reaction at the air−aqueous interface, 12 how changing solvent polarity can influence the CO 2 capture processes, 13 and the role of interface in CO 2 capture using ionic liquids were also studied using MD simulations. 14,15 The behavior of AAs at interfaces has been studied using SFG spectroscopy mainly in the context of their role as building blocks for peptides and proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Later, the same group used first-principles molecular dynamics along with enhanced sampling methods to study the interfacial stability of a CO 2 -MEA zwitterion. 4 Unlike the case in bulk water, they found that the zwitterion and carbamate ions are relatively unstable at the vapor/amine aqueous interface, which emphasizes the importance of understanding the differences between homogeneous and heterogeneous CO 2 conversion processes.…”
mentioning
confidence: 99%
“…Interestingly, they found that lowering the polarity of the solvent by adding chloroform, which would decrease the solubility of MEA in the solution, would at the same time favor CO 2 -MEA conformers that are more prone to mineralization. Later, the same group used first-principles molecular dynamics along with enhanced sampling methods to study the interfacial stability of a CO 2 -MEA zwitterion . Unlike the case in bulk water, they found that the zwitterion and carbamate ions are relatively unstable at the vapor/amine aqueous interface, which emphasizes the importance of understanding the differences between homogeneous and heterogeneous CO 2 conversion processes.…”
mentioning
confidence: 99%